A 2‐year dyadic longitudinal study of mothers' and fathers' marital adjustment when caring for a child with cancer. Issue 10 (30th June 2016) - Burns, W.; Péloquin, K.; Sultan, S.; Moghrabi, A.; Marcoux, S.; Krajinovic, M.; Sinnett, D.; Laverdière, C.; Robaey, P.
Abstract: Objective: Studies examining interrelationships within parental couples confronted with pediatric cancer are scarce. This study explored dyadic longitudinal associations between both partners' family functioning and mood at diagnosis, and marital adjustment 2 years later. Method: Parents of children ( n  = 47 couples) with acute lymphoblastic leukemia (ALL) completed the Family Well‐Being Assessment and Profile of Mood States‐Bipolar Form at diagnosis, and the Locke–Wallace Marital Adjustment Test 2 years post diagnosis. Multilevel linear models using the actor–partner interdependence model (APIM) and controlling for baseline marital adjustment were conducted to evaluate within subject and dyadic longitudinal effects. Results: For mothers, better marital adjustment 2 years post diagnosis was associated with perception of greater family support and less role conflict and role overload at diagnosis. For fathers, better marital adjustment 2 years post‐diagnosis was associated with perception of less role conflict, greater role ambiguity, and being more tired at diagnosis, as well as their partner's perception of less role conflict at diagnosis. Conclusions: These findings highlight the importance of considering both partners' perspectives in understanding marital adjustment across treatment phases in parents of children with ALL. Early interventions for couples should be tailored to meet each partner's needs in order to foster resilience within the couple.